Penyisihan Logam Mangan (Mn) Dalam Air Tanah Dengan Proses Aerasi Menggunakan Tray Aerator - Handika Resvandry; Edward HS; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Groundwater is the largest source of water that contain manganese (Mn). One method that can be used to decrease manganese (Mn) is aeration using tray aerator. Tray aerator can increase the air contact time with water by letting the water flow down on a cross section. This study aims to determine the ability of tray aerator in removing manganese (Mn) concentrations in variations number of trays (3, 5, and 7 tray) and hole diameter (2 mm, 4 mm, and 6 mm). The results showed that the best removal efficiency of manganese (Mn) was occurred in variation of 7 tray diameter of 2 mm pit at 99,65%.Keywords: Aeration, Groundwater, Manganese, Tray aerator